Biochar and Energy Production from Rice Husk and Corncob in Karawang: A Techno-Enviro Analysis - Siantar, Gabriella A L; Surjosatyo, Adi (Prosiding SNTTM, 2024)
The world is facing increasing challenges in sustainable energy production and waste management. This study presents a techno-environmental analysis of biochar and energy production from rice husks and corncob in Karawang, Indonesia, through co-gasification. A parametric study using Aspen Plus simulation shows that biochar yield is sensitive to temperature and  equivalence ratio (ER). Specifically, corncob gasification at 450 degrees Celsius yields the highest amount of biochar. Additionally, the study finds that increases in temperature and ER lead to higher syngas and lower heating value (LHV). A life cycle assessment was conducted to evaluate three scenarios: 100% rice husk, 100% corn cob, and a 50% combination of rice husk and corncob for biochar application as carbon sequester. The findings indicate that the 50% mixing ratio has the most positive impact on global warming potential, with a carbon offset of - 170,134 kg CO2eq per 1000 kg of biochar applied to soil. The results provide valuable insights into environmental impacts of utilizing these agricultural residues for renewable energy generation and biochar production.